2014
DOI: 10.1016/j.fct.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory activity of orphan drug Elmiron® in female B6C3F1/N mice

Abstract: Interstitial cystitis (IC) is a chronic disorder characterized by bladder discomfort and urinary urgency in the absence of identifiable infection. Despite the expanding use in treatment of IC and other chronic conditions, the effects of Elmiron® treatment on immune system remain unknown. Therefore, female B6C3F1/N mice were orally administered Elmiron® daily for 28-days at doses of 63, 125, 250, 500 or 1000 mg/kg to evaluate its immunomodulatory effects. Mice treated with Elmiron® had a significant increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“… 61 Regarding the mechanism of action of oral PPS, in female B6C3F1/N mice, its administration stimulated the immune system, increasing the numbers of specific cell populations and enhancing macrophage phagocytosis and natural killer (NK) cell activity. 62 Recently, however, results from a randomized, double-blind, placebo-controlled study of patients with symptoms consistent with IC did not demonstrate a treatment effect with PPS when compared with placebo at the currently established dose. 63 …”
Section: Level 1 Evidence Treatmentsmentioning
confidence: 98%
“… 61 Regarding the mechanism of action of oral PPS, in female B6C3F1/N mice, its administration stimulated the immune system, increasing the numbers of specific cell populations and enhancing macrophage phagocytosis and natural killer (NK) cell activity. 62 Recently, however, results from a randomized, double-blind, placebo-controlled study of patients with symptoms consistent with IC did not demonstrate a treatment effect with PPS when compared with placebo at the currently established dose. 63 …”
Section: Level 1 Evidence Treatmentsmentioning
confidence: 98%
“…Although pharmacological therapies have shown some benefit in control of IC/BPS symptoms, they may have a negative impact on the patient due to the inherent potential of adverse events [ 9 ]. In vivo studies using mouse models have shown that pentosan polysulfate may cause uncontrolled activation of immune function, which may lead to chronic inflammation, hypersensitivity, or autoimmunity [ 10 ]. As IC/BPS therapies continue to evolve, triple-targeted therapy using gabapentin, amitriptyline, and a nonsteroidal anti-inflammatory drug (NSAID) have demonstrated improved clinical outcomes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%